Technologische Dramen: Radiokulturen und Medienwandel in Benin (Westafrika) - Grätz, Tilo (transcript, 2014)
New media laws and technologies are currently changing radio in West Africa. Tilo Grätz analyzes this change using the example of the appropriation of radio technologies in Benin. He shows that the processes take place in the interplay of producers, listeners, and technical capabilities under the influence of institutions of media politics. Local radio cultures develop which manifest themselves in typical subjects, program formats, and everyday radio use practices. The most successful programs are interactive and facilitate discussion on social and political as well as personal problems. Technological dramas (Pfaffenberger) accompany the varied development of Beninese radio cultures.